Gender dimensions in the complexity of managing forest resource: learning from Berau District, Indonesia - Sakuntaladewi, Niken (Centre for Research and Development on Social, Economy, Policy and Climate Change, Indonesia, 2019)
Presented by Niken Sakuntaladewi (CRDSEPCC), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.